2019
DOI: 10.1016/j.joca.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in stiffness and biochemical composition of the pericellular matrix as a function of spatial chondrocyte organisation in osteoarthritic cartilage

Abstract: Objective: During osteoarthritis (OA), chondrocytes seem to change their spatial arrangement from single to double strings, small and big clusters. Since the pericellular matrix (PCM) appears to degrade alongside this reorganisation, it has been suggested that spatial patterns act as an image-based biomarker for OA. The aim of this study was to establish the functional relevance of spatial organisation in articular cartilage. Method: Cartilage samples were selected according to their predominant spatial cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…In a previous study, we had already shown that the PCM progressively loses its characteristic biomechanic properties alongside cellular rearrangement 39 . We had further demonstrated that, accompanying these pattern changes, the two main PCM components—collagen type VI and perlecan—undergo progressive destruction 39 . In the present study, the current knowledge of PCM degradation on the basis of cellular spatial organization is further expanded upon by additionally investigating its components collagen type III, biglycan, and fibrillin‐1.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…In a previous study, we had already shown that the PCM progressively loses its characteristic biomechanic properties alongside cellular rearrangement 39 . We had further demonstrated that, accompanying these pattern changes, the two main PCM components—collagen type VI and perlecan—undergo progressive destruction 39 . In the present study, the current knowledge of PCM degradation on the basis of cellular spatial organization is further expanded upon by additionally investigating its components collagen type III, biglycan, and fibrillin‐1.…”
Section: Introductionmentioning
confidence: 54%
“…Discs of articular cartilage from 127 patients (approximately 30 discs per target analysis) were cut, sorted, and assigned to their predominant cellular pattern organization as described previously 39 . Using a custom‐fabricated device, cartilage was cut in the horizontal plane (ie, parallel to the superficial zone) to obtain discs of 300 µm in thickness and 4 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,16,17,[20][21][22][23][24][25] Only at certain stages during the progression of OA can rapid colony-like proliferation of chondrocytes occur in cartilage tissue,which we call chondrocyte colony-like clusters. [26][27][28][29][30][31][32] However, the signi cance of chondrocyte colony-like cluster formation in cartilage during OA progression remains unclear. 27,33,34 Some studies have suggested that chondrocyte colony-like cluster formation in cartilage is a compensatory response by which the body compensates for the decrease in the number of chondrocytes during the development of OA.…”
Section: Introductionmentioning
confidence: 99%